The Effectiveness of Using Number Head Together (NHT) Strategy in Teaching Speaking at First Grade of MAS Darul Makmur Sungai Cubadak - Hidayati, Miftahul (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2022)
This research background was triggered by students problems at the first grade of MAS Darul Makmur Sungai Cubadak. Based on preliminary observation and interviews with the teacher, the researcher found several problems in teaching speaking. First students` were less motivated in learning speaking because of a lack of vocabulary. Second, students who do not understand the learning material feel embarrassed to ask their teachers and friends, or students just keep silent when they don't understand the learning material. Third, in groups, not all students discuss learning material and only a few students participate in the discussion. The research question of this research is how effective using the Number Head Together strategy is in teaching speaking. The purposes of this study were to identify the effectiveness of the use of the Number Head Together (NHT) strategy in teaching speaking at MAS Darul Makmur Sungai Cubadak.This research used mix method with first grade MAS Darul Makmur Sungai Cubadak students as the research population. The sample in this research was all students at first grade. In this study, the researcher used total sampling. Data collection was carried out by interview, observation, and documentation. In the interview, the researchers interviewed the teachers who used the Number Head Together in teaching speaking. There are 15 questions asked by the researcher to the teacher. In the observation, the researcher used an observation checklist. In addition to documentation, the data is taken from students' scores in speaking. Then the student's score was analyzed by the researcher.  Based on the result of the study, it was revealed that Number Head Together strategy was effective in teaching speaking. This can be seen from the results of the researcher interview with the teacher who used Number Head Together strategy, and also it can be seen from the result of the observation sheet and was supported by an average student learning outcomes in speaking which reached 82.770%. It can be said that the Number Head Together Strategy was in very effective category.